Preschoolers' vocabulary acquisition in Chile: the roles of socioeconomic status and quality of home environment - Lohndorf, Regina T.; Vermeer, Harriet J.; Carcamo, Rodrigo A.; Mesman, Judi (My University, 2018)
Preschoolers' vocabulary acquisition sets the stage for later reading ability and school achievement. This study examined the role of socioeconomic status (SES) and the quality of the home environment of seventy-seven Chilean majority and Mapuche minority families from low and lower-middle-class backgrounds in explaining individual differences in vocabulary acquisition of their three-and-a-half-year-old children. Additionally, we investigated whether the relation between SES and receptive and expressive vocabulary was mediated by the quality of the home environment as the Family Investment Model suggests. The quality of the home environment significantly predicted receptive and expressive vocabulary above and beyond ethnicity, SES, parental caregiver status, and quantity of daycare. Furthermore, the quality of the home environment mediated the relation between SES and expressive and receptive vocabulary acquisition.
Keywords: None